Seroimmunologicaf aspect of TORCH infection in infer le woman - Budi Mulyono, Budi Mulyono (Universitas Gadjah Mada, 1998)
Infertility is a problem among child bearing age couples. TORCH infection as one of causative factors infertility must be investigated of its role. The objective of this study is to compare TORCH antibodies seropositivity of infertile cases to pregnant women. Sera from 67 infertile women and 21 pregnant women were used for the study. The results are as follows: the mean of IgG anti-CMV and IgG anti-HSV2 titre of Infertile group are significantly higher than titre of pregnant group. The individual who has been exposed to HSV-2 will have a higher risk to Infertility than who has not. Coincidence infections of TORCH are similar between two groups. It can be concluded that problems of TORCH in infertility must be inferred to any other related factors.Key Word: TORCH - infertility - seroimmunological test - IgG anti-CMV - IgG anti-HSV2